2000
DOI: 10.1097/00005650-200005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Responses to Health Plan Report Cards in Two Markets

Abstract: Although the 2 samples differed markedly, their responses to report cards were similar. Exposure and helpfulness were related more to employee preferences for the type of information than to their health care decision needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…15 This overall rating correlates highly with several specific quality questions from the CAHPS ® survey 13 Several other studies have examined health plan quality information awareness and use. For example, see Knutson et al (1998), Short et al (2002), Fowles et al (2000), and Schultz et al (2001). 14 Dafny and Dranove (2005) study both market-based learning and learning from report cards in the context of Medicare beneficiaries' enrollment decisions in HMOs.…”
Section: Information Seekingmentioning
confidence: 99%
“…15 This overall rating correlates highly with several specific quality questions from the CAHPS ® survey 13 Several other studies have examined health plan quality information awareness and use. For example, see Knutson et al (1998), Short et al (2002), Fowles et al (2000), and Schultz et al (2001). 14 Dafny and Dranove (2005) study both market-based learning and learning from report cards in the context of Medicare beneficiaries' enrollment decisions in HMOs.…”
Section: Information Seekingmentioning
confidence: 99%
“…La construcción de este índice de reputación considera como atributos medidas de resultado en calidad asistencial y en seguridad del paciente, la percepción del paciente (satisfacción) y de los ciudadanos (confianza), actuaciones para mitigar el impacto ambiental, buenas prácticas de gestión económica y de personal y la capacidad del hospital para la investigación e innovación. La difusión de estas evaluaciones entre la población se espera que tenga un efecto beneficioso en la mejora de la calidad asistencial 3,[24][25][26][27] , aunque existen dudas sobre la mejor forma de llevar a cabo esta difusión para no generar confusión entre los ciudadanos 19,28 . En este estudio han participado profesionales de la gestión, calidad y seguridad de las instituciones sanitarias de nuestro país, propiciándose un consenso sobre la estructura recomendable para elaborar un índice reputación de los hospitales.…”
Section: Discussionunclassified
“…A number of previous studies 2- 6 have shown that publicising performance information on health plans or hospitals had only a limited effect on consumer choice. We believe that the key reasons for our positive findings are (1) the physician specific information was easy to understand and (2) the people had the freedom to make such choices.…”
Section: Discussionmentioning
confidence: 99%
“…While efforts to release hospital performance data to the public have been made in the last decade in the US and UK, 1 recent reviews and studies suggest that the public release of hospital performance data has had only a limited impact on the selection of physicians, hospitals, and healthcare plans by consumers. [2][3][4][5][6] Results from field surveys of insurance beneficiaries also show that only a small proportion of the respondents used the released information to aid in decision making. [7][8][9] There are two possible explanations for this-a lack of familiarity of consumers with comparative healthcare quality information 7 10 and a limited number of providers from which they can choose.…”
mentioning
confidence: 99%